NO to Violence Against AnyWoman! - Paim, Polianna; García, Laura Sánchez; Pereira, Elissandra Gabriela (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
COVID-19’s social distance increased domestic violence (DV). In Brazil, in spite of the existence of services to denounce DV, women who do not communicate through the Brazilian-Portuguese language (Pt-Br) are, in fact, excluded as users. As a previous stage to development of a mobile application to denounce DV by women who are illiterate in Pt-Br, being them Brazilian or immigrant and including Brazilians with disabilities, a study on Brazilian mobile services to denounce DV by women who are Deaf was performed. This paper presents the study’s results, requirements and shows that applications are not inclusive. The requirements triggered the need for future Participatory Design activities together with each one and all women involved, in order to guarantee that their other cultural and social specificities are addressed. These activities are part of the feminist interaction design agenda, within which the application design process will be seen.